2018
DOI: 10.1017/s1463423618000129
|View full text |Cite
|
Sign up to set email alerts
|

Does a modified mindfulness-based cognitive therapy (MBCT) course have the potential to reduce stress and burnout in NHS GPs? Feasibility study

Abstract: Background: There is a crisis of low morale among NHS GPs, with most describing their

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(88 citation statements)
references
References 22 publications
(37 reference statements)
0
88
0
Order By: Relevance
“…Scores for the quality of the studies ranged between 6.5 and 14.5 on the MERSQI scale; the mean score was 9.9, reflecting average quality (Table S2) . The eligible studies included seven randomised controlled trials (RCTs), three non‐randomised controlled trials (CTs), 12 pre‐post studies, and two qualitative interview studies (Table ). Of the RCTs and CTs, four studies employed a waitlist control condition, four studies employed a passive control condition, and two studies exposed controls to protected free time during the intervention period .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scores for the quality of the studies ranged between 6.5 and 14.5 on the MERSQI scale; the mean score was 9.9, reflecting average quality (Table S2) . The eligible studies included seven randomised controlled trials (RCTs), three non‐randomised controlled trials (CTs), 12 pre‐post studies, and two qualitative interview studies (Table ). Of the RCTs and CTs, four studies employed a waitlist control condition, four studies employed a passive control condition, and two studies exposed controls to protected free time during the intervention period .…”
Section: Resultsmentioning
confidence: 99%
“…Response rates for survey completion were between 75% and 100% in seven studies, between 50% and 74% in three studies, and below 50% (or were not reported) in 14 studies . Eight were multicentre studies . Indicators of instrument validity (eg internal consistency, content or criterion validity) were inconsistently reported (Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mindfulness programmes have achieved tangible effects in reducing burnout in healthcare personnel (Eby et al, 2019;Eriksson, Germundsjö, Åström, & Rönnlund, 2018;Hamilton-West, Pellatt-Higgins, & Pillai, 2018;Lu et al, 2019) and even in nursing students (Song & Lindquist, 2015). Their positive effect has also been demonstrated in studies with nurses, although the types of intervention vary and different effect sizes have been reported (Dos Santos et al, 2016;Slatyer, Craigie, Heritage, Davis, & Rees, 2018).…”
mentioning
confidence: 99%
“…30 31 Accordingly, several studies show similar results for MBIs in physicians. [32][33][34][35][36][37][38] In addition to improving physicians' mental health and well-being these studies also show that MBIs improve the quality of treatment. [39][40][41][42] Consistent with these findings, preliminary studies reported beneficial effects of MBIs in residents.…”
Section: Introductionmentioning
confidence: 99%